Groundwater, the state, and the creation of irrigation communities in Llanos del Caudillo, Spain - Closas, Alvar (2018)
This article explores the creation of new groundwater-based irrigation communities as a result of the internal colonisation projects of Franco’s government in the 1950s in La Mancha, Central Spain. The literature on Spain’s hydraulic mission has mainly focused on the use and mobilisation of large surface water projects as part of a state-driven modernisation mission promoting irrigation and water management infrastructure without much contextualisation or focus on its operationalisation at the local level. This paper complements this body of work by examining the local socio-political development of government-led irrigation plans in the colonisation town of Llanos del Caudillo. Moreover, the study of Spain’s hydro-politics and colonisation efforts usually focuses on surface water infrastructure while the public promotion of groundwater use has always been relegated to a second place, as it was mainly driven by private initiative. This paper substantiates the role of groundwater within Spain’s hydraulic mission and production of state-sponsored irrigated landscapes.